Synergistic Impairment of the Neurovascular Unit by HIV-1 Infection and Methamphetamine Use: Implications for HIV-1-Associated Neurocognitive Disorders - Nikolai Fattakhov; Silvia Torices; Michael Stangis; Minseon Park; Michal Toborek (Viruses, 2021)
The neurovascular units (NVU) are the minimal functional units of the blood–brain barrier (BBB), composed of endothelial cells, pericytes, astrocytes, microglia, neurons, and the basement membrane. The BBB serves as an important interface for immune communication between the brain and peripheral circulation. Disruption of the NVU by the human immunodeficiency virus-1 (HIV-1) induces dysfunction of the BBB and triggers inflammatory responses, which can lead to the development of neurocognitive impairments collectively known as HIV-1-associated neurocognitive disorders (HAND). Methamphetamine (METH) use disorder is a frequent comorbidity among individuals infected with HIV-1. METH use may be associated not only with rapid HIV-1 disease progression but also with accelerated onset and increased severity of HAND. However, the molecular mechanisms of METH-induced neuronal injury and cognitive impairment in the context of HIV-1 infection are poorly understood. In this review, we summarize recent progress in the signaling pathways mediating synergistic impairment of the BBB and neuronal injury induced by METH and HIV-1, potentially accelerating the onset or severity of HAND in HIV-1-positive METH abusers. We also discuss potential therapies to limit neuroinflammation and NVU damage in HIV-1-infected METH abusers.